Role of Routine Histopathology of Gallbladder Specimen from Gallstone Disease to Detect Unsuspected Carcinoma - Islam, Md Jahidul; Akter, Shaheen; Talukder, Abdur Rabban; Haque, Md Shariful (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: Carcinoma of the gallbladder is a malignancy with very high mortality rate. Unfortunately, our common practice to discard gallbladder specimens after cholecystectomy in unsuspected malignancy. This results in missing some premalignant conditions and early carcinomas. This study was conducted to find out the incidence of unsuspected gallbladder carcinoma from cholecystectomy patients in routine histopathology of specimens and analyze their clinico-pathological features. Methods: This was a two years cross sectional study included 542 patients with acute or chronic cholecystitis secondary to cholelithiasis operated by cholecystectomy. All cases of carcinoma gallbladder, on clinical grounds or confirmed by radiology were excluded. Gallbladders showing gross abnormalities suggestive of localized or infiltrative malignancy during surgery were also excluded. All gallbladder specimens were send for histopathology examination. Results: Over a period of two years, five hundred and fortytwo patients with symptomatic gallstones were admitted for Journal of Bangladesh College of Physicians and Surgeons Vol. 37, No. 4, October 2019 cholecystectomy. The male to female ratio was 1:3. Most of the patients (26.49%) were found in fourth decade of life. Majority of patients (93.54%) presented with upper abdominal pain of varying duration. All the specimens were sent for histopathology. Four hundred sixty cases (84.87%) showed chronic cholecystitis (including intestinal metaplasia and dysplasia). Seventy of the cases (12.92%) showed evidence of acute cholecystitis (including empyema and mucocele). Twelve gallbladders (2.21%) showed evidence of adenocarcinoma of varying differentiation along with cholelithiasis. Conclusion: Incidental diagnosis of carcinoma gallbladder is not rare. We strongly recommend to submit all cholecystectomy specimens routinely to histopathology laboratory, as this is the only means by which subclinical malignancies can be detected at an early stage. J Bangladesh Coll Phys Surg 2019; 37(4): 186-190